(untitled) (Encuentros, 2020)
This article has the fundamental purpose of characterizing the guiding principles of the professional profile of a social communicator and journalist in the context of the labor market in the Eje Cafetero area, and it´s various actors that have contributed to labor and market environments. As a situational and territorial study, the labor conditions of the geographical context are addressed throughout the last two decades in this part of the country to understand the occupational field, and thus, obtain pertinent information regarding labor insertion, the step of the professional practice to the professional life of the academic programs of Social Communication and Journalism. Keywords: communicator profile, labor market, training, occupational sector.